Helmet initiative programs in Malaysia. - Radin Sohadi, Radin Umar; Hashim, Ahmad Hariza; K.C Mani, Kulanthayan; Law, Teik Hua; Abu Hassan, Musa; Mohd Taib, Mohd Nasir (Universiti Putra Malaysia, 2005)
Motorcyclists make up nearly 49% of the road user population and constitute 60% of the fatalities on Malaysian roads. The majority of them die due to head injuries. One of the reasons for this is the improper usage of safety helmets. To encourage higher usage of safety helmets a systematic safety campaign on proper usage of helmets was carried out. Attention was given to head injuries risks and the benefits of correct usage of helmets using the strategic campaign media namely television, newspapers and outdoor billboards. In addition to this initiative, a revised result helmet standard was implemented and new children's helmets were introduced. These initiatives have so far resulted in a higher compliance rate of proper usage of safety helmet, better understanding and more positive attitudes among riders on the risk of head injuries in Malaysia.